Embedding Evidence-Based Practice in Teaching-Learning Strategies in Undergraduate Physiotherapy Clinical Training in Abu Dhabi: Clinical Educators’ Perspective - Gabor, Marian Grace (2023)
Background: Evidence-based practice (EBP) is an essential attribute in the healthcare setting. Prior to conducting this study, there was a lack of contextualized information as to how introduction and enhancement of EBP among physiotherapy students are carried over into undergraduate clinical training. Purpose: The aim of this study was to understand teaching-learning strategies that enhance physiotherapy undergraduates’ evidence-based practice during clinical training from the perspective of clinical educators. Methods: A qualitative approach was used which involved key-informant in-depth interviews with physiotherapy clinical educators of physiotherapy students in Abu Dhabi (n=12). Clinical educator participants are physiotherapy clinicians in private hospitals and rehabilitation centres in Abu Dhabi. The audio-recorded interviews were transcribed and underwent thematic analysis using NVivo 12. Results: Thematic analysis revealed that clinical educators recognized seven strategies aimed at enhancing students’ evidence-based practice during clinical placement as: (1) case presentation, (2) problem-based learning, (3) skills demonstration, (4) shadowing, (5) following patient’s progress, (6) exposure to a variety of patient cases, and (7) exposure to different clinical educators. Conclusion: Clinical educators of physiotherapy students in Abu Dhabi employ a variety of teaching-learning strategies that enhance the adoption of an evidence-based physiotherapy practice by students during undergraduate clinical training.